2016
DOI: 10.1155/2016/9050828
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates Contrast-Induced Nephropathy in Diabetic Rats: The Role of Interleukin-33 and Oxidative Stress

Abstract: Background. Inflammation and oxidative stress (OxS) contribute to the pathogenesis of diabetic kidney disease (DKD) and contrast-induced nephropathy (CIN). Patients with DKD were found to be more prone to CIN. Interleukin-33 (IL-33) is a proinflammatory cytokine, but its role in DKD and CIN is unknown. Methods. Thirty male Sprague-Dawley rats were enrolled. The first group was comprised of healthy rats (HRs), whereas the other four groups were made up of diabetic rats (DRs), diabetic rats with contrast-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 40 publications
2
33
0
2
Order By: Relevance
“…Such findings support several studies in this context. Melatonin insufficiency which was associated with prolonged light exposure at night have been evidenced to cause several diseases such as; neurodegenerative diseases [19] diabetic kidney disease [20], cancer [21], Parkinson's disease [22] Alzheimer's disease [23], and others health problems [24].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings support several studies in this context. Melatonin insufficiency which was associated with prolonged light exposure at night have been evidenced to cause several diseases such as; neurodegenerative diseases [19] diabetic kidney disease [20], cancer [21], Parkinson's disease [22] Alzheimer's disease [23], and others health problems [24].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin elevates numerous antioxidant enzymes, such as SOD, peroxidase, GSH and lipid peroxidase [29]. Melatonin easily crosses cell membranes and leads to protection against free radical-induced damage to biomolecules [173].…”
Section: Melatonin Is An Appropriate Agent For the Treatment Of Diabementioning
confidence: 99%
“…Onk et al [173] found enhanced IL-33 levels in the kidney tissue following contrast-induced nephropathy (CIN) in diabetic rats; administration of melatonin in these animals considerably attenuated kidney tissue concentrations of inflammatory cytokines, oxidative stress biomarkers, and IL-33, indicating potential roles of melatonin in the treatment of diabetic nephropathy. Melatonin also reduced serum creatinine in rats with diabetic nephropathy.…”
Section: Melatonin Is An Appropriate Agent For the Treatment Of Diabementioning
confidence: 99%
“…Melatonin can ameliorate many complications of diabetes mellitus, including retinopathy [28] and nephropathy [29]. In vivo studies have demonstrated that melatonin has antioxidant and anti-inflammation activities in diabetic nephropathy [10,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have demonstrated that melatonin has antioxidant and anti-inflammation activities in diabetic nephropathy [10,29,30]. In an in vitro diabetic nephropathy model, Ji et al [31] showed that melatonin has anti-apoptotic effects in angiotensin II-induced podocyte injury.…”
Section: Discussionmentioning
confidence: 99%